Creative Practices in Mathematics Teaching: results of planning through Universal Design for Learning - Raksa, Paula Regina; Góes, Heliza Colaço; Góes, Anderson Roges Teixeira (Educação Matemática Debate, 2025)
We analyze the excerpt of a creative pedagogical practice based on Universal Design for Learning (UDL) in Mathematics lessons for a 5th grade of Elementary School. It is part of a master's thesis at the Federal University of Paraná. The aim is to present how the integration of creativity and the principles of UDL transforms teaching, with a focus on teaching flexibility and student engagement. The study highlights inclusion in education as an ethical commitment, emphasizing practices that respect students' individualities. The pedagogical practice from the UDL perspective stimulated creativity and expanded access to knowledge, connecting Mathematics to everyday life.